1979
DOI: 10.1136/bmj.2.6189.515
|View full text |Cite
|
Sign up to set email alerts
|

Large-bowel obstruction caused by cancer: a prospective study.

Abstract: Summary and conclusionsPatients with obstructing large-bowel cancer may be treated by primary tumour resection or the conventional staged tumour resection, and a prospective study comparing these two treatments was carried out. The postoperative outcome in 174 patients (of whom 90 underwent primary and 47 staged tumour resection) showed that the overall mortality was similar in both groups but that the duration of hospital stay in patients who underwent primary tumour resection was half that of those who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(42 citation statements)
references
References 4 publications
2
39
1
Order By: Relevance
“…Although some authors have suggested that advanced age is not a reason for a poor prognosis in patients with complicated colorectal cancer [5, 21], we have found that this factor was associated with a significantly higher mortality, in accordance with other reports [14, 22]. Although female sex was linked with higher mortality, this factor did not reach statistical significance in the univariate analysis.…”
Section: Discussionsupporting
confidence: 74%
“…Although some authors have suggested that advanced age is not a reason for a poor prognosis in patients with complicated colorectal cancer [5, 21], we have found that this factor was associated with a significantly higher mortality, in accordance with other reports [14, 22]. Although female sex was linked with higher mortality, this factor did not reach statistical significance in the univariate analysis.…”
Section: Discussionsupporting
confidence: 74%
“…Günteret al 36 Fielding and Wells 12 Fielding et al 35 Huddy et al 23 7 Two stages 8 of 31 (26) 4 of 22 (18) 8 of 24 (33) 1 of 15 (7) 8 of 63 (13) 1 of 19 (5) (4) 13 of 47 (28) 0 of 12 (0) 8 of 58 (14) Three stages Risk difference (%) Risk difference (%) Saida et al 42 Law et al 40 Tomiki et al 41 Carne et al 38 Baque et al 37 Johnson et al 39 Fiori et al Endoscopic stenting tends to produce better results than urgent surgical intervention in terms of mortality and so may play an increasing role in decompression of acute colonic obstruction. Surgery for colonic obstruction depends on the cause and location of the obstruction, the extent of disease, co-morbidities and clinical status, and the experience of the surgeon.…”
Section: Referencementioning
confidence: 98%
“…The mortality rate for emergency surgery of the colon in recent series lies between 15 and 40% [2,3], whilst that for elective colonic surgery has been improving steadily to 0.5-5% [4,5]. The excess mortality in the emergency group does not appear to be due to age, since no statistically significant differences in age at presenta tion can be shown between the elective and emergency groups [3,8], so other factors must operate, in particular the hypovolaemic state of the obstructed patient, predis posing to renal and cardiovascular morbidity in the post operative period.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality for elective colonic resection in most mod em series lies between 0.5 and 5%, whilst emergency resection of the acutely obstructed colon in a comparable age-group can lead to a mortality 10 times as great [1][2][3][4], and unfortunately 15-20% of colonic carcinomas present this way [5].…”
Section: Introductionmentioning
confidence: 99%